Implementation of Problem Solving Methods in Elasticity Course - Hasnah Dewi Kadir; Muhammad Arsyad; Dewi Hikmah Marisda (Universitas Muhammadiyah Makassar, 2020)
The low number of students who have grades above the minimal mastery learning in physics subjects is the focus of the problem in this study. The study was a real experimental study using a posttest-only design. This study consisted of two classes, the control class, and the trial class. The purpose of this study to describe how much the physics learning outcomes of students have taught without using problem-solving methods and students who taught using problem-solving techniques. The instrument used in this study was a physics learning achievement test that had been tested for validity and reliability by two experts. The results showed that the average score in the control class was 12,86 and in the experimental class was 14,69.